From the Tallest to (One of) the Fattest: The Enigmatic Fate of the American Population in the 20th Century - John Komlos; Marieluise Baur (Center for Economic Studies and ifo Institute (CESifo), 2003)
Within the course of the 20th century the American population went through a metamorphosis from being the tallest in the world, to being among the most overweight. The American height advantage over Western and Northern Europeans was between 3 and 9 cm in the middle of the 19th century. Americans were also underweight. However, today, the exact opposite is the case as the Dutch, Swedes, and Norwegians are the tallest, and the Danes, British and Germans - even the East-Germans - are also taller, towering over the Americans by as much as 3-7 cm. Americans also live shorter. The hypothesis is worth considering that this adverse development is related to the greater social inequality, an inferior health-care system, and fewer social safety nets in the United States than in Western and Northern Europe, in spite of higher per capita income. The West- and Northern European welfare states, with cradle to grave health and unemployment insurance currently provide a more propitious environment for the biological standard of living than its US counterpart.
Keywords: 330